Stimulation of Enterotoxin B Production II. Synthetic Medium for Staphylococcal Growth and Enterotoxin B Production - Wu, Cheng-Hsien (1971)
A relatively large amount of enterotoxin B (125 μg/ml) was produced in a synthetic medium composed of amino acids, inorganic salts, and vitamins. This medium was prepared on the basis of the utilization of the various amino acids by Staphylococcus aureus strain S-6 throughout the growth cycle. Arginine appeared to be essential for enterotoxin production. The pattern of enterotoxin production in the synthetic media appeared to differ from that in complex media.